2021
DOI: 10.14203/beritabiologi.v20i1.3866
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF CHROMIUM STRESS ON MICRO-ANATOMICAL PROFILE OF CHILI (Capsicum annuum L.)

Abstract: Chromium contamination can affect morphological, physiological, and anatomical changes, especially in chili vegetative organs. This research aims to understand micro-anatomical structure of the vegetative organs of chili subjected to chromium stress. The aim of the research is to know whether there is a micro-anatomical character difference between contaminated and uncontaminated chromium. The experimental methods using a completely randomized design (CRD). The independent variable is five levels of chromium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Previous studies reported that application of sodium azide and cytokinin on black rice triggered the increase on chlorophyll content, but decreased the length of epidermal cells [10]. Similarly, Fitrianto et al [11] found that application of chromium in chili reduced the epidermal cell thickness, mesophyll, width and number of stomata. Apart from the increase of epidermal thickness, the application of OPEB ash nanoparticle tended to reduce the chlorophyll content (both a and b) compared to the control (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies reported that application of sodium azide and cytokinin on black rice triggered the increase on chlorophyll content, but decreased the length of epidermal cells [10]. Similarly, Fitrianto et al [11] found that application of chromium in chili reduced the epidermal cell thickness, mesophyll, width and number of stomata. Apart from the increase of epidermal thickness, the application of OPEB ash nanoparticle tended to reduce the chlorophyll content (both a and b) compared to the control (Fig.…”
Section: Resultsmentioning
confidence: 87%